(untitled) (Journal of Politics and International Studies, 2024)
Undeniably and more evidently, space in the twenty first century is gradually transforming into a significant region that embraces conflicts, especially between the present superpowers: The United States of America, China and Russia. This work examines the relatively mild competition of this “Cosmic Showdown;” in other words, to determine how these nation-states seek to deploy space as a strategic resource for the purpose of overpowering and dominating global geopolitics properties. Since this study uses an empirical study in space exploration and geopolitics, both the policy declarations and the analysis of the academic literature reflects a systematic approach towards space exploration. It synchronizes the benefits of technological advancement, influences resulting from space commerce, camaraderie and hostility of discretionary space societies. For these reasons, the paper concludes logically that as it is considered as a global common, cyberspace remains in the process of becoming a competitive space. It explains the existence of geostrategic factors in space activity and acknowledges the importance of the change of legislation and related global processes that will address new issues. It may be useful to politicians, researchers and other interested parties due to the absence of research on space geopolitics.